Catalytic wet air oxidation of aniline on transition metal modified MCM-41 catalysts - Gomes, Helder (2010)
Transition metal (Cu, Cr and V) MCM-41 catalysts were prepared hydrothermally and characterized by X-ray diffraction (XRD), scanning electron microscopy/energy dispersive X-ray (SEM/EDX), inductively coupled plasma-atomic emission spectroscopy (ICP-AES) and N2 adsorption-desorption analysis at -196ºC. The catalysts were tested in the catalytic wet air oxidation (CWAO) of aniline aqueous solutions at 200ºC and 6.9 bar of oxygen partial pressure. The (Cu)MCM-41 catalyst showed the best performance with respect to combined activity and selectivity for aniline conversion to nonorganic compounds. After 2 h of reaction, 96% aniline conversion and 76% of selectivity were attained. Under the employed reaction conditions, leaching of copper was detected in small extent. However, heterogeneous catalytic activity was proved and attributed to copper oxide anchored to MCM-41.